The Leadership Role of The Village Head in Improving Public Services in The Kalibobo Village Office, Nabire District, Nabire Regency - Petrus Yeimo; Aris Widodo (Budapest International Research and Critics University, 2022)
The Village Head as a Leader has the ability to influence employees in his work environment at the Kalibobo Village Office, in working both office work in his field of work and also to be able to provide services to the public to the maximum, so that with the abilities possessed by employees, they can show performance because when people are satisfied with the results of the work given, the employee is considered capable and responsible for the work he is doing. The research location is at the Kalbobo Village Office using a total sample of 18 employees who are used as respondents, the research method uses quantitative descriptive methods based on questionnaires that are processed according to the answers from respondents. The results showed that the Head of Kalibobo Village had carried out his duties optimally as a leader because in carrying out his duties he followed the duties and functions as a leader but there were also obstacles faced in carrying out his duties but the Village head could respond wisely so that the results were satisfactory so that when serving the community with the level of need which are diverse, of course, are supported by the cooperation of employees in the Kalibobo Village Office environment, so that the expected results can provide satisfaction in serving the community to the maximum.